Application of a scoring evaluation of the state of preservation of historic residential and garden sites. case study: Wicimice and Iglice (Zachodniopomorskie Voivodeship) - Michał Uruszczak (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The article aims to apply a scoring evaluation method to residential and garden sites and evaluate historic, aristocratic parks in Wicimice and Iglice (Zachodniopomorskie Voivodeship, Poland). The results are intended to demonstrate the effectiveness of the employed method, identify its shortcomings and advantages, and help improve it. In addition, the work’s objective is to tell the story of the objects and depict their current situation.